Designing a methodological system for the development and support of gifted and motivated students - Mambetalina, Aliya; Nurkeshov, Timur; Satanov, Arstan; Karkulova, Aigul; Nurtazanov, Erkulan (Frontiers in Psychology, 2023)
The paper was intended to develop a new methodological system and test its impact on the development of motivation and giftedness among children. The experiment was conducted among 1,200 children from grades 3, 7, and 10 by researchers from the Daryn Republican Applied Research Center of the Ministry of Education and Science of the Republic of Kazakhstan and L.N. Gumilyov Eurasian National University. The teaching methodology involved: interactive technologies; developing projects with faculty members; and conducting electives in the exact sciences, humanities, natural sciences, and the creative arts. The experiment lasted 4 months. Before and after the experiment, all respondents were evaluated by their instructors according to the following four criteria: academic giftedness, creative giftedness, social giftedness, and intellectual giftedness. The overall result demonstrated an increase in the level of giftedness to above-average values. Motivation levels observed among respondents in grades 3, 7, and 10 were 1.71; 1.72, and 1.54, respectively. The level for this criterion also reached above-average values. This implies that this technique is effective. This technique can already be applied not only in special schools for gifted children, but also in general educational institutions to achieve better results.